2013
DOI: 10.1021/jf305468f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antimicrobial Evaluation of Neovestitol and Vestitol Isolated from Brazilian Red Propolis

Abstract: The objective of this study was to evaluate anti-inflammatory and antimicrobial activities of neovestitol and vestitol isolated from Brazilian red propolis (BRP). BRP ethanolic extract (EEP), neovestitol, and vestitol were evaluated by anti-inflammatory properties using a neutrophil migration assay. The antimicrobial activity was evaluated by minimal inhibitory and bactericidal concentrations (MIC and MBC) against Streptococcus mutans , Streptococcus sobrinus , Staphylococcus aureus , and Actinomyces naeslundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 32 publications
5
140
1
15
Order By: Relevance
“…10,15,16,23,32 In these studies, ethanolic extracts of propolis, or its bioactive fractions, were applied topically to the molars of rats twice a day for a period of 4 to 5 weeks. Overall, the authors observed anti-caries activity similar to that of Duraphat ® .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,15,16,23,32 In these studies, ethanolic extracts of propolis, or its bioactive fractions, were applied topically to the molars of rats twice a day for a period of 4 to 5 weeks. Overall, the authors observed anti-caries activity similar to that of Duraphat ® .…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the molecular weight of chitosan used in the formulation, which is different from that generally used in other studies (using low molecular weight) to test the antimicrobial activity of dental products. 7,10,14,33,35,36,37,38,39,40 Changes in the molecular weight of the chitosan used may have precluded polymeric film formation, which is necessary to mediate product adhesion to the teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Algumas atividades biológicas são atribuídas à PVA, entre elas as atividades antimicrobiana (ALENCAR et al, 2007), antifúngica (DAUGSCH et al, 2007) e antiinflamatória (BUENO-SILVA et al, 2013). Tendo em mente essas especiais atividades, a própolis vermelha de Alagoas também pode ser utilizada em formulações de produtos odontológicos como resinas dentárias compostas.…”
Section: Introdução Sobre Própolisunclassified